Computational analysis of tensile damage and failure of mineralized tissue assisted with experimental observations. (March 2020) - Misra, Anil; Sarikaya, Rizacan
In this study, deformation and failure mechanisms of mineralized tissue (bone) were investigated both experimentally and computationally by performing diametral compression tests on millimetric disk specimens and conducting finite element analysis in which a granular micromechanics-based nonlinear user-defined material model is implemented. The force–displacement relationship obtained in the simulation agreed well with the experimental results. The simulation was also able to capture location of the failure initiation observed in the experiment, which is inside out from the hole along the loading axis. Furthermore, propagation of micro-sized cracks into failure was observed both in the experiment using simultaneous slow-motion microscopy imaging and in the simulation analyzing the local distortion and local volume change within the specimen. The anisotropy evolution was found to be significant around the hole along the loading axis by evaluating the anisotropy index computed using finite element results. In conclusion, this work revealed that the prediction capability of granular micromechanics-based user-defined nonlinear material model (UMAT) is promising considering the match between the results and observations from the physical experiment and finite element analysis such as force–displacement relationship and failure initiation/pattern. This work has also shown that the tensile damage and failure of mineralized tissues can be characterized using diametral compression (split tension) test.